Constructing highly tribopositive elastic yarn through interfacial design and assembly for efficient energy harvesting and human-interactive sensing - Bai, Zhiqing; He, Tianyiyi; Zhang, Zixuan; Xu, Yunlong; Zhang, Zhi; Shi, Qiongfeng; Yang, Yanqin; Zhou, Buguang; Zhu, Minglu; Guo, Jiansheng; Lee, Chengkuo (Nano energy, 2022)
Fibers/yarns with superior triboelectrification and robust stretchability are considered indispensable building blocks for booming fiber-shaped wearable electronics. Here, a new class of highly tribopositive elastic yarn is developed through an interfacial design and assembly using polyethylene oxide/waterborne polyurethane/alliin composite as stretchable tribomaterial and polyethyleneimine/multiwalled carbon nanotubes/phytic acid polyionic nanomaterial as electrode. The contact triboelectrification and mechanical stretch behaviors of yarn are separately modulated by multiple functional groups coordination and hydrogen bond crosslinking/electrostatic interactions, realizing efficient charge transfer/accumulation capability and stretchable robustness. The optimized yarn TENG with single-electrode mode can deliver a high voltage of 137 V and power density of 2.25 mW/m by varying content of alliin and controlling the thickness of tribocomposite, which is superior to fiber-shaped TENGs reported thus far. Importantly, the device exhibits good electrical output stability and durability in multiple dynamic deformations or long-term service. The yarn can be easily integrated into the stretchable fabric for motion energy harvesting and can also be used as pressure/strain sensor to realize whole-body physiological signals detection and human-interactive sensing in virtual reality space. This work provides feasible proposal for the design of stretchable high-performance fiber TENGs and greatly promotes the advancement in wearable energy/sensing/interactive systems. A highly tribopositive elastic yarn with efficient charge transfer and accumulation is developed through interfacial design and assembly technology. The cooperation of multiple functional groups and multilayered interface interaction realize high positive triboelectrification and robust extensibility. This yarn can be used for collecting biomechanical energy, detecting physiological signals, and realizing human-interactive sensing, exhibiting promising applications in intelligent wearable systems. [Display omitted] •Highly tribopositive elastic yarn with charge transfer/accumulation capability is proposed via interfacial design/assembly.•Functional groups and hydrogen bonding/electrostatic interactions modulate triboelectrification and mechanical behavior.•Yarn TENG is optimized by investigating the effect of alliin content and thickness of tribolayer on electrical performance.•The yarn can collect biomechanical energy, detect whole-body physiological signals, and realize VR human-interactive sensing.